Reversible dinitrogen binding to [Cp′Fe(NHC)] associated with an N2-induced spin state change. Issue 53 (10th April 2017) - Reiners, Matthias; Baabe, Dirk; Zaretzke, Marc-Kevin; Freytag, Matthias; Walter, Marc D.
Abstract : Reversible N2 coordination to [Cp′Fe(IiPr2 Me2 )] induces a spin-state change. Abstract : The 15-valence electron (VE), high-spin ( S = 3/2) half-sandwich complex [Cp′Fe(IiPr2 Me2 )] (3 ; IiPr2 Me2 = 1, 3-di-iso-propyl-4, 5-dimethylimidazol-2-yildene) reversibly coordinates N2 to form the 17VE, low-spin ( S = 1/2) compound [Cp′Fe(IiPr2 Me2 )(η 1 -N2 )] (4 ).